Study on demulsifier formulation for treating Malaysian crude oil emulsion - Mat, Hanapi; Samsuri, Ariffin; Wan Abdul Rahman, Wan Aizan; Othman, Norasikin; Chieng, Yu Yuan; Jong, Siaw Chuan; Zulkania, Ariany (Universiti Teknologi Malaysia, 2005)
Water in oil emulsion occurs at many stages in the production and treatment of crude oil. About two third of petroleum production of every oil field exists in the form of water in oil emulsion. The emulsion stability results from the presence of interfacial barrier preventing coalescence of the dispersed water droplets. This is due to the present of polar components such as asphaltenes, resins, wax and naphtenic acids in the crude oil. Therefore before transporting or refining the oil, it is essential to separate the water for economic and operational reasons. Minimizing the water level in the oil reduces pipeline corrosion and maximizes pipeline usage. The most effective method to overcome the problem is to demulsify the crude by using demulsifiers. The demulsifiers will destabilize the interfacial film between the droplets. It has been reported that the combination of oil-soluble demulsifiers and water-soluble demulsifiers produced great result in water separation. From the screening process of single oil-soluble demulsifiers, the most effective chemicals as demulsifier are TOMAC, hexylamine and dioctylamine while methyl methacrylate, butyl acrylate and acrylic acid are the most effective chemicals in water-soluble group. The new formulation of demulsifier was formulated by using Statistical Analysis System software. From this analysis, the optimum concentration needed for TOMAC, hexylamine, dioctylamine, methyl methacrylate, butyl acrylate and acrylic acid are 48.7 ppm, 0 ppm, 8 ppm, 48.2 ppm, 26.5 ppm and 29.9 ppm, respectively. The combination of these chemicals resulted 53.7% to 60.4% water separation from the emulsion system. It was found that this formulation is better than other commercial demulsifier formulation. This new formulation was found to be effective for demulsification of water-in-oil emulsion of Tabu, Seligi, Guntong, Semangkok, Irong Barat and Tapis fields and single emulsion system. In order to obtain better understanding and results, optimizing on agitation and temperature conditions, the mechanism demulsification study are recommended for further study.